Media capture in a democracy : the role of wealth concentration - Giacomo Corneo (Center for Economic Studies and ifo Institute (CESifo), 2005)
Since objective news coverage is vital to democracy, captured media can seriously distort collective decisions. The current paper develops a voting model where citizens are uncertain about the welfare effects induced by alternative policy options and derive information about those effects from the mass media. The media might however secretly collude with interest groups in order to influence the public opinion. In the case of voting over the level of a productivity-enhancing public bad, it is shown that an increase in the concentration of firm ownership makes the occurrence of media bias more likely. Although media bias is not always welfare worsening, conditions for it to raise welfare are restrictive.
Keywords: D72; H41; 330; mass media; public bads; voting; wealth inequality; Kommunikationsmedien; Informationsverhalten; Demokratie; Wirtschaftskonzentration; Wirtschaftliche Macht; Interessenpolitik; Public Choice; Wohlfahrtseffekt; Theorie